2016
DOI: 10.3892/mmr.2016.5986
|View full text |Cite
|
Sign up to set email alerts
|

A novel PDGF receptor inhibitor-eluting stent attenuates in-stent neointima formation in a rabbit carotid model

Abstract: A novel drug-eluting stent (DES) is required to target vascular smooth muscle cells (SMCs) without harming endothelial cells (ECs). Platelet-derived growth factor (PDGF) is critical for the proliferation and migration of SMCs. Sunitinib [a PDGF receptor (PDGFR) tyrosine kinase inhibitor]-eluting stents may therefore inhibit neointimal formation. The aim of the present study was to examine the stent-based delivery of sunitinib in a rabbit carotid model; in addition, the effects of sunitinib were evaluated in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…2B). Activation of the PDGF receptor was observed in our previous publication 3 mo after BMS implantation (8). We hypothesized that various growth factors that are released after mechanical expansion might be crucial for SMC The detailed mechanisms underlying the effects of SFES on SMC phenotypic modulation require an indepth investigation before its clinical application.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…2B). Activation of the PDGF receptor was observed in our previous publication 3 mo after BMS implantation (8). We hypothesized that various growth factors that are released after mechanical expansion might be crucial for SMC The detailed mechanisms underlying the effects of SFES on SMC phenotypic modulation require an indepth investigation before its clinical application.…”
Section: Discussionmentioning
confidence: 89%
“…After sorafenib (catalog no. 8705, Cell Signaling Technology) treatment, MTT assays were performed as previously described to determine SMC and REC proliferation (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that, at the site of injury, activated ECs, platelets, monocytes and leukocytes express and/or secrete pro-inflammatory molecules such as E-and P-selectin, IL-6, IL-8, platelet-derived growth factor (PDGF), transforming growth factor beta 1 (TGF-β1) and basic fibroblast growth factor (bFGF) thereby stimulating local inflammation and VSMC dedifferentiation, proliferation and migration -cellular processes that are all crucial for the development of intimal hyperplasia (Figure 1) [26,[34][35][36][37][38][39][40][41][42][43][44]. It has previously been shown that targeting those growth factors and/or their receptors in vivo affects the development of both venous and arterial neointimal hyperplasia [45][46][47][48]. Early inward remodelling appears to be predictive of subsequent VGF [49] and limiting intimal hyperplasia in both ex vivo and in vivo studies has been demonstrated as a potentially successful approach to improving graft patency [50,51].…”
Section: Intimal Hyperplasia/neointimal Formationmentioning
confidence: 99%
“…Coated stents were prepared as we previously reported. 14 The RhoA inhibitor rhosin (Merck, Darmstadt, Germany) dissolved in 100 mL of ethanol was mixed with Muko jelly (Jiangsu Province Jianerkang Medical Dressing Co, Ltd, Jintan, China) to a final concentration of 2 mg/g of jelly. Each balloon-mounted stent (diameter, 2 mm; length, 20 mm) was individually dipped in rhosin jelly to produce a thin stent coating weighing approximately 0.015 g. The stents were air dried to completely evaporate the solvent for 24 hours.…”
Section: Article Highlightsmentioning
confidence: 99%